Análisis de clústers jurisprudenciales en el área andina: acercamiento mixto al ius constitutionale commune (Tema Central) - Guerrero Salgado, Efrén Ernesto (2021)
This document proposes a mixed type approach to the jurisprudence of three American constitutional courts, regarding the use of binding jurisprudence issued from the Inter-American Human Rights System (SIDH), in order to empirically demonstrate the existence of a Ius Constitucionale Commune. This concept is a phenomenon of construction of a legal community around the American Convention on Human Rights and the inter-American corpus iuris, supported by the idea of standards derived from international law and taken advantage of by the High Courts. This text explores this possibility, through a survey of qualitativequantitative information on the jurisprudence of the Peruvian, Colombian and Ecuadorian Constitutional Courts during 2020, processed by the methodology of social network analysis (social network analysis). The data obtained demonstrate: a) a more or less constant use of the jurisprudence of the IAHRS; and b) the factual possibility of this phenomenon is an element that can be studied in our region as a sample of an authentic integrationist structure of constitutional law.